The effects of anodal tDCS over the supplementary motor area on gait initiation in Parkinson’s disease with freezing of gait: a pilot study - Lu, Chiahao (J Neurol, 2018)
OBJECTIVE: We investigated if anodal transcranial direct current stimulation (A-tDCS), applied over the supplementary motor areas (SMAs), could improve gait initiation in Parkinson’s disease (PD) with freezing of gait (FOG). METHODS: In this double-blinded cross-over pilot study, ten PD with FOG underwent two stimulation sessions: A-tDCS (1 mA, 10 min) and sham stimulation. Eight blocks of gait initiation were collected per session: (1) pre-tDCS, with acoustic cueing; (2) pre-tDCS, self-initiated (no cue); and (3–8) post-tDCS, self-initiated. Gait initiation kinetics were analyzed with two-way repeated measures ANOVAs for the effects of A-tDCS. RESULTS: A-tDCS did not significantly improve the magnitude or timing of anticipatory postural adjustments or the execution of the first step during self-initiated gait compared with baseline measures (p > .13). The lack of significant change was not due to an inability to generate functional APAs since external cueing markedly improved gait initiation (p < .01). CONCLUSIONS: A single dose of A-tDCS over the SMAs did not improve self-initiated gait in PD and FOG. Alternative approaches using a different dose or cortical target are worthy of exploration since individuals demonstrated the capacity to improve. SIGNIFICANCE: Neuromodulation strategies tailored to facilitate SMA activity may be ineffective for the treatment of gait initiation impairment in people with PD and FOG.